2016
DOI: 10.1038/srep28543
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Origin of Challenge of Realizing Metallaphosphabenzenes: Unfavorable 1,2-Migration in Metallapyridines Becomes Feasible in Metallaphosphabenzenes

Abstract: Metallabenzenes have attracted considerable interest of both theoretical and experimental chemists. However, metallaphosphabenzene has never been synthesized. Thus, understanding the origin of the challenge of synthesizing metallaphosphabenzene is particularly urgent for experimentalists. Now density functional theory (DFT) calculations have been carried out to examine this issue. Our results reveal that the 1,2-migration in metallapyridines is unfavorable whereas such a 1,2-migration in metallaphosphabenzenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…For instance, with the aid of computational studies, Jia and co-workers successfully isolated the first rhenabenzenes by introducing alkoxy groups to the rhenabenzene ring . Calculations have suggested that certain palladiabenzenes and rhodiabenzenes might be isolable, η 5 metal indenyl and metal fluorenyl complexes could be applied as starting materials for the synthesis of metallanaphthalenes and metallaanthracenes, respectively, , and some metallaphosphabenzenes might be stable and prepared from half-phosphametallocene. Unfortunately, these predictions remain to be confirmed experimentally. In addition, reaction mechanism studies rely more and more on computational methods.…”
Section: Conclusion and Outlookmentioning
confidence: 99%
“…For instance, with the aid of computational studies, Jia and co-workers successfully isolated the first rhenabenzenes by introducing alkoxy groups to the rhenabenzene ring . Calculations have suggested that certain palladiabenzenes and rhodiabenzenes might be isolable, η 5 metal indenyl and metal fluorenyl complexes could be applied as starting materials for the synthesis of metallanaphthalenes and metallaanthracenes, respectively, , and some metallaphosphabenzenes might be stable and prepared from half-phosphametallocene. Unfortunately, these predictions remain to be confirmed experimentally. In addition, reaction mechanism studies rely more and more on computational methods.…”
Section: Conclusion and Outlookmentioning
confidence: 99%
“…Metallaphosphabenzenes have not yet been realized experimentally. However, their stability and a possible synthetic route have recently been investigated computationally and this may prove to be a fruitful avenue of research in the future.…”
Section: Heterometallabenzenesmentioning
confidence: 99%
“…Besides, our interest in NHC-catalyzed reactions also prompts us to investigate the origin of selectivities for the competing reactions in detail19202122232425262728293031. In the present study, the commonly used DFT theoretical investigation3233343536373839404142 on the reaction between R1 (in which Ar 1  = para chlorphenyl) and R2 (in which Ar 2  = phenyl) catalyzed by NHC depicted in Fig. 1, was pursued in order to shed light on details of each elementary step at the molecular level and to reach more comprehensive understanding to the enantioselectivity of this interesting reaction.…”
mentioning
confidence: 93%